2016
DOI: 10.1007/s00410-016-1238-8
|View full text |Cite
|
Sign up to set email alerts
|

Li zoning in zircon as a potential geospeedometer and peak temperature indicator

Abstract: 920 to 650 °C, calculated diffusivities are in agreement with a previously established Arrhenius relationship calibrated on trace-element-poor Mud Tank zircon. Our revised Arrhenius relationship that includes both datasets is:We also observed that synthetic sector-zoned zircon exhibits near-step-function Li concentration profiles across sectors that correlate with changes in the rare earth element (REE) and P concentrations. This allowed us to examine how Li diffusion might couple with REE diffusion in a manne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 47 publications
2
41
1
Order By: Relevance
“…However, this mechanism has not been observed by current experimental studies (Cherniak and Watson, 2010;Trail et al, 2016), both of which reported fast Li diffusion in zircon. Cherniak and Watson (2010) conducted "in" diffusion experiments using REE-depleted Mud Tank zircons, and thus their experiments are unlikely to have evaluated charge coupling effects.…”
Section: Experimental Perspectives On LI Diffusion In Zirconcontrasting
confidence: 57%
See 4 more Smart Citations
“…However, this mechanism has not been observed by current experimental studies (Cherniak and Watson, 2010;Trail et al, 2016), both of which reported fast Li diffusion in zircon. Cherniak and Watson (2010) conducted "in" diffusion experiments using REE-depleted Mud Tank zircons, and thus their experiments are unlikely to have evaluated charge coupling effects.…”
Section: Experimental Perspectives On LI Diffusion In Zirconcontrasting
confidence: 57%
“…Cherniak and Watson (2010) conducted "in" diffusion experiments using REE-depleted Mud Tank zircons, and thus their experiments are unlikely to have evaluated charge coupling effects. Using Lu-and P-doped synthetic zircons, Trail et al (2016) carried out "in" diffusion and heating experiments, and their "in" diffusion experiments showed no discernable difference in Li diffusivity when compared to Cherniak and Watson's results. These Hoskin et al (2000) experimental studies reveal that another substitution mechanism for Li in zircon that does not involve coupling with REE and Y creates a fast diffusion mode.…”
Section: Experimental Perspectives On LI Diffusion In Zirconmentioning
confidence: 94%
See 3 more Smart Citations